Concept of Destination Image Exploration on Tourist’s Risk Perception - Virginia Mandasari; Dominikus Aditya Fitriyanto; Yusvika Ratri Harmunisa; Rikantini Widiyanti (Future Science, 2022)
Positive information and feedback for tourists should be provided through the marketing information medium to increase visits to tourist attractions. One of the most important determining factors is the credence of such information obtained by tourists. Tourists can access marketing information through social media, both in the formal and informal communication realms. The information obtained from the medium then forms a mental image that reinforces tourists' perceptions of risk and influences their decision to travel. Considering this, the purpose of this study is to find out the understanding of experts and research regarding the feelings of anxiety of tourists' travel with risk perception marketing information media. In this research, the author uses a qualitative research method using a library approach.